DIALOG:TRIBUTE UNTUK PAUS EM. BENEDIKTUS XVI - Markus Solo Kewuta (Ledalero Institute of Philosophy and Creative Technology (IFTK Ledalero), Indonesia, 2013)
Shortly after he was chosen as Bishop of Rome in April 2005, Benedict XVI took a number of steps towards a new dynamics in inter-faith dialogue. He began by setting down fundamental principles, namely knowing and appreciating one’s own faith as the essential condition for sincere cross-religious encounters. That is why, as a prominent dogmatic theologian, in his theological approach he not infrequently laid down clear boundaries, even in grey areas which sometimes drew strong rejection, for a real theological dialogue is not easy. But, according to Benedict XVI, this is the road we have to travel to arrive at a true dialogue, rather than simply politeness or “lip service”. During his period of service, Catholic-Muslim Forum I and II were created with their final declarations; if followed through globally, there would be no need for any more disputes or enmity between Catholics and Muslims. Unfortunately, reality is different. Today Bishop of Rome Francis wishes to follow-up this mission with a different language and emphasis. The core is the same, that through friendship and the principle of reciprocity, Catholic and Muslim peoples respect and understand each other without fear, for we are all brothers and sisters.